PENGALAMAN IBU DENGAN STATUS HIV/AIDS DALAM PENERAPAN POLA PENGASUHAN ANAK DI RSUD CILEGON TAHUN 2019 - Rahmawati, Dewi; Firdaus, Irfan; Ernawati, Eka; Afriyani, Firda (Universitas Islam Negeri Alauddin Makassar, 2020)
Mothers with positive HIV status risk to failure in role adaptation, which causes confusion in carrying out multiple roles, which results in the inaccuracy of parents in implementing parenting styles for their children. The purpose of this study was to explore in depth the meaning of the experience of mothers with HIV / AIDS as a parent in implementing parenting. The method used in this research is a qualitative method using a descriptive phenomenology approach. While the data collection method used is by using in-depth interviews until 40-60 minutes. The participants were five people who were registered as patients at the Poli Flamboyan RSUD Kota Cilegon. We used phenomenological data analysis with Collaizi’s approach. The researcher applied the ethical principles in the form of Respect for Autonomy and self-determination, Confidentiality and anonymity, and Protection from discomfort and harm. The results obtained five themes which significantly describes wail of the wife with HIV / AIDS status, unbelieve in HIV / AIDS status, fear of being stigmatized, the impact of HIV on the adoption of parenting styles and feelings of failure to become mothers. There needs to be education or counseling for parents with HIV / AIDS regarding choosing the implementation of parenting for children along with the Peer Support Group (KDS) program for people with HIV / AIDS to increase the spirit of ODHA to continue their life.Keywords: HIV/AIDS, Mother, Parenting